(untitled) (Journal of Informatics Education and Research, 2025)
The it sector in india is perceiving unprecedented growth, escorted by intense competition to attract extremely skilled professionals. The deficiency of competent talent & the rising demand for expert digital skills have forced organizations to distinguish themselves through robust employer_branding. Employer_branding reflects how potential personnel perceive the firm as a place to work. It incorporates the company’s principles, ethics, work environment, compensation structure & overall reputation. Talent_ acquisition is no longer limited to filling vacancies; it includes building long-term relations, creating a robust employer value proposition & ensuring an engaging employee practice. In the it sector, where skilled experts have multiple opportunities, employer_branding serves as a strategic recruitment instrument that influences job seekers’ decisions. In an increasingly competitive information technology (it) environment, organizations are purposefully focusing on